2011
DOI: 10.1089/tmj.2010.0174
|View full text |Cite
|
Sign up to set email alerts
|

E-Health Policy and Deployment Activities in Europe

Abstract: Governments that included e-health applications in policy documents rather early have adopted more telematics applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Furthermore, a study by Lang and Mertes [ 62 ] demonstrated that the prevailing orientation of dominating political parties can influence how innovative health technologies are accessed and used at the State level, resulting in variations in the distribution of these resources. In a similar discussion, Han et al [ 60 ] refer explicitly to the social determinants of health theory, which describes the unequal distribution of health as a result of socioeconomic conditions that are largely constructed by social policy [ 65 ], to stress the significance of a geographical patterning of health influencing variations in access and use of innovative health technologies.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a study by Lang and Mertes [ 62 ] demonstrated that the prevailing orientation of dominating political parties can influence how innovative health technologies are accessed and used at the State level, resulting in variations in the distribution of these resources. In a similar discussion, Han et al [ 60 ] refer explicitly to the social determinants of health theory, which describes the unequal distribution of health as a result of socioeconomic conditions that are largely constructed by social policy [ 65 ], to stress the significance of a geographical patterning of health influencing variations in access and use of innovative health technologies.…”
Section: Resultsmentioning
confidence: 99%
“…ICT goods are intended to fulfill the function of information processing and communication by electronic means [23,24]. …”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, political influences have played a major role in the transition management and implementation of technology (Lang & Mertes, 2011). For example, the Guardian News mentioned that the US government's shutdown of federal departments "would result in hundreds of thousands of federal workers being placed on unpaid leave, after House Republicans refused to pass a budget unless it involved a delay of Barack Obama's signature on healthcare reforms" (Lewis, 2013, p.14).…”
Section:  the Impact Of Managerial Practices On The Adoption Of Emrmentioning
confidence: 99%